Der Sonderkulturanbau in Südwest-Australien und seine südeuropäische Trägerschaft - Roth, Klaus (ERDKUNDE, 1984)
Having encountered favourable geo-ecological conditions there, the extent of specialized cropping in south-western Australia - which in 1981/82 occupied a mere 0.25% of the agricultural land but achieved 8.7% of Western Australia’s agricultural output - is chiefly determined by the metropolitan market of Perth in the environs of which the greater part of the wine, fruit, agrumen and vegetable area is situated. In addition to these small horticultural firms in the vicinity of the city, which are based upon irrigation, there are also several narrowly defined areas of cultivation in the extreme south west. Here medium-sized and large holdings combine stock raising with the in part unirrigated cultivation of specialized crops. In the face of the lack of a suitable labour-force and the high cost of wages, the profitability of the holdings cultivating specialized crops is ensured by their specific practitioners. Investigation of the family names of the membership list of the Market Gardener Association in Perth (1981) has shown that 57% of the farmers are immigrants from Southern Europe, namely Italians and Dalmation Croats. Thanks to their physical adaptation to the climatic conditions and their farming origins, the Southern Europeans - who by a variety of features can be distinguished from the British Australians as a group with a particular way of life - are the best guarantors for the care of labour-intensive cultivars. As self-employed farmers they take the place of the non-white proletariat of farm-labourers characteristic of many regions with a similar production structure in the New World. With further acculturation, however, their pre-eminent position will be lost. In conclusion, the present decline of specialized cropping in south-western Australia is explained by the urban effect of displacement and the higher costs of production. By comparison with related areas of the same landscape zone (California,the South African Cape Area) it operates under the worst conditions.